The prevalence and distribution of food sensitization in European adults. Issue 3 (26th December 2013) - Burney, P. G. J.; Potts, J.; Kummeling, I.; Mills, E. N. C.; Clausen, M.; Dubakiene, R.; Barreales, L.; Fernandez‐Perez, C.; Fernandez‐Rivas, M.; Le, T.‐M.; Knulst, A. C.; Kowalski, M. L.; et al.
Abstract Background Complaints of 'food allergy' are increasing. Standardized surveys of IgE sensitization to foods are still uncommon and multicountry surveys are rare. We have assessed IgE sensitization to food‐associated allergens in different regions of Europe using a common protocol. Methods Participants from general populations aged 20–54 years in eight European centres (Zurich, Madrid, Utrecht, Lodz, Sophia, Athens, Reykjavik and Vilnius) were asked whether they had allergic symptoms associated with specific foods. Weighted samples of those with and without allergic symptoms then completed a longer questionnaire and donated serum for IgE analysis by ImmunoCAP for 24 foods, 6 aeroallergens and, by allergen microarray, for 48 individual food proteins. Results The prevalence of IgE sensitization to foods ranged from 23.6% to 6.6%. The least common IgE sensitizations were to fish (0.2%), milk (0.8%) and egg (0.9%), and the most common were to hazelnut (9.3%), peach (7.9%) and apple (6.5%). The order of prevalence of IgE sensitization against different foods was similar in each centre and correlated with the prevalence of the pollen‐associated allergens Bet v 1 and Bet v 2 (r = 0.86). IgE sensitization to plant allergen components unrelated to pollen allergens was more evenly distributed and independent of pollen IgE sensitization (r = −0.10). The most common foods containing allergens not cross‐reacting with pollens were sesame, shrimp and hazelnut. Discussion IgE sensitization to foods is common, but varies widely and is predominantly related to IgE sensitization to pollen allergens. IgE sensitization to food allergens not cross‐reacting with pollens is rare and more evenly distributed.